Pelajaran dari Apartheid: Membangun Kewarganegaraan yang Adil melalui Pemahaman Antropologis - Berlian, Nur; Febriani, Rika (Journal of Civic Education, 2025)
This paper explores the link between anthropological views on race and citizenship politics, focusing on South Africa's Apartheid. Before the 1800s, non-European societies were often unfairly labeled "primitive," justifying European colonization and a "civilizing mission". Apartheid exemplifies a racial policy where a white minority controlled power, discriminating against the black majority. Understanding these historical anthropological perspectives is crucial for grasping their impact on citizenship and racism. The study uses a literature review, drawing from journals and research. Data from various sources are systematically organized by themes like Apartheid's history, South African citizenship, and racism. Qualitative data analysis is conducted through thematic interpretation, identifying patterns and narratives. Inductive qualitative methods are used to draw conclusions, demonstrating the enduring impact of apartheid policies on South African society and thought. This paper highlights the critical need to understand colonialism's and Apartheid's legacies for effective citizenship education, aiming to build just and inclusive societies.